Self-Reference Effect Induced by Self-Cues Presented During Retrieval - He, Liguo; Han, Wei; Shi, Zhan (Frontiers in Psychology, 2021)
The self-reference effect (SRE) refers to better memory for self-relevant than for other-relevant information. Generally, the SRE is found in conditions in which links between the stimuli and the self are forged in the encoding phase. To investigate the possibility that such conditions are not prerequisites for the SRE, this research developed two conditions by using two recognition tasks involving abstract geometric shapes (AGSs). One was the cue-in-encoding condition in which self- and other-cues were presented to construct links with AGSs during the encoding phase, and the other was the cue-in-retrieval condition in which self- and other-cues were presented to construct links with AGSs during the retrieval phase. The SRE was found in both conditions. The findings reveal that self-cues merely presented during the retrieval phase are sufficient to induce the SRE. Links between the stimuli and the self constructed during the encoding phase may not be necessary prerequisites for the SRE.